Аналог теоремы Ролля для дифференциальных операторов и интерполирование L-сплайнами - Новиков, С.И. (Український математичний журнал, 1993)
An analog of the Rolle theorem is established for linear differential operators with continuous periodic coefficients. By using this result, exact values of the deviations of interpolationalL-splines are obtained on certain classes of functions given by a linear differential operator.